Novel electrospun gelatin/oxycellulose nanofibers as a suitable platform for lung disease modeling - Švachová, Veronika; Vojtová, Lucy; Pavliňák, David; Vojtek, Libor; Sedláková, Veronika; Hyršl, Pavel; Alberti, Milan; Jaroš, Josef; Hampl, Aleš; Jančář, Josef (Materials science & engineering. C, Materials for biological applications, 2016)
Novel hydrolytically stable gelatin nanofibers modified with sodium or calcium salt of oxycellulose were prepared by electrospinning method. The unique inhibitory effect of these nanofibers against Escherichia coli bacteria was examined by luminometric method. Biocompatibility of these gelatin/oxycellulose nanofibers with eukaryotic cells was tested using human lung adenocarcinoma cell line NCI-H441. Cells firmly adhered to nanofiber surface, as determined by scanning electron microscopy, and no signs of cell dying were detected by fluorescent live/dead assay. We propose that the newly developed gelatin/oxycellulose nanofibers could be used as promising scaffold for lung disease modeling and anti-cancer drug testing.
Keywords: Escherichia coli; nádory plic; nádorové buněčné linie; celulosa oxidovaná; lidé; Cellulose, Oxidized; Adenocarcinoma; Nanofibers; nanovlákna; želatina; Humans; Lung Neoplasms; Gelatin; adenokarcinom; Cell Line, Tumor